Analysis Of Historical and International Best Practices In The Field Of Developing A Healthy Religious Outlook In The Individual - Atakulova Nargizakhan Alijonovna (Genius Journals, 2024)
This paper examines historical and international best practices in developing a healthy religious outlook in individuals. Drawing upon insights from diverse cultural, religious, and philosophical traditions, the paper explores the significance of fostering a healthy religious outlook for individual well-being and social cohesion. Historical perspectives highlight timeless principles and practices for spiritual growth and ethical living, while international best practices offer innovative strategies for promoting religious well-being in diverse cultural contexts. The paper also discusses challenges and opportunities in promoting a healthy religious outlook and proposes recommendations for educators, policymakers, religious leaders, and practitioners interested in enhancing spiritual fulfillment, mental health, and social harmony.
Keywords: healthy religious outlook; religion; spirituality